Distinct Blood and Visceral Adipose Tissue Regulatory T Cell and Innate Lymphocyte Profiles Characterize Obesity and Colorectal Cancer - Donninelli, Gloria; Del Cornò, Manuela; Pierdominici, Marina; Scazzocchio, Beatrice; Varì, Rosaria; Varano, Barbara; Pacella, Ilenia; Piconese, Silvia; Barnaba, Vincenzo; D’Archivio, Massimo; Masella, Roberta; Conti, Lucia; et al. (Frontiers in Immunology, 2017)
Visceral adipose tissue (VAT) is a main site where metabolic and immunologic processes interplay to regulate, at local and systemic level, the inflammatory status and immune response. Obesity-associated inflammation and immune dysfunctions are inextricably linked to tumor but, in spite of intense efforts, the mechanisms underpinning this association remain elusive. In this report, we characterized the profile of VAT-associated and circulating innate lymphocyte and regulatory T (Treg) cell subsets underlying inflammatory conditions, such as obesity and colorectal cancer (CRC). Analysis of NK, NKT-like, γδ and Treg cell populations in VAT and blood of healthy lean subjects revealed that CD56hi NK and OX40+ Treg cells are more abundant in VAT with respect to blood. Conversely, CD56dim NK and total Treg cells are most present in the circulation, while γδ T lymphocytes are uniformly distributed in the two compartments. Interestingly, a reduced frequency of circulating activated Treg cells, and a concomitant preferential enrichment of OX40-expressing Treg cells in VAT, were selectively observed in obese subjects, and directly correlated with body mass index. Likewise, CRC patients were characterized by a specific enrichment of VAT-associated NKT-like cells. In addition, obese and CRC-affected individuals shared a significant reduction of the Vγ9Vδ2/γδ T cell ratio at systemic level. The alterations in the relative proportions of Treg and NKT-like cells in VAT were found to correlate with the content of pro- and anti-inflammatory polyunsaturated fatty acids (PUFA), respectively. Overall these results provide evidence for distinct alterations of the immune cell repertoire in the periphery with respect to the VAT microenvironment that uniquely characterize or are shared by different inflammatory conditions, such as obesity and CRC, and suggest that VAT PUFA composition may represent one of the factors that contribute to shape the immune phenotypes.